Natural history of multiple sclerosis - Ebers, G (2001)
Studies which have attempted to define the outcome ot multiple sclerosis (MS) have methodologic difficulties arising from patient referral biases and the length of follow-up required, which make prospective studies of an inception cohort unrealistic. Means to improve the validity of retrospective natural history studies are suggested. Results of existing series are summarized and compared. Survival is only rarely shortened by MS, but disability to the point of requiring aids for ambulation occurs in 30-70% of patients by 15 years from onset of symptoms. Disagreement as to the percentage of patients who are ultimately bedridden by MS likely arises in large part due to differences in patient ascertainment and follow-up. The need to develop early clinical markers for the patient at high risk for rapid development of major disability is stressed.